1990
DOI: 10.1007/bf00177832
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitivity testing of human gliomas using a fluorescent microcarrier technique

Abstract: This report describes a new fluorescent microcarrier cytostasis assay. Human glioma cell lines and primary cultures were attached to microcarrier tissue culture beads and treated with various chemotherapeutic drugs. After treatment, the cells were labelled with two vital fluorescent dyes in order to measure cellular viability. The uptake of hydroethidine and Hoechst 33342 was evaluated alone and in combination as probes for determining metabolic activity and cellular proliferation. Hydroethidine was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Moreover, the extent of HE uptake and accumulation may be dependent not only on the dye concentration and incubation time, but also on the metabolic state of the cells [19]. HE was used in the investigation of antiproliferative compounds [24-26] and in other biological studies as a vital stain [27-31]. …”
Section: Evolution Of He From a Vital Dye To Superoxide Probementioning
confidence: 99%
“…Moreover, the extent of HE uptake and accumulation may be dependent not only on the dye concentration and incubation time, but also on the metabolic state of the cells [19]. HE was used in the investigation of antiproliferative compounds [24-26] and in other biological studies as a vital stain [27-31]. …”
Section: Evolution Of He From a Vital Dye To Superoxide Probementioning
confidence: 99%
“…As shown in Fig. 1, C6 was the Sariban et al 1987HTSCA 10 Panasci et al 1985Bowles et al 1990;Nikkhah et al 1992;Jordan et al 1992 [ 35 Results of primary cultures were within the range of the results for dierent long-term-cultured cell lines. Comparing the agents showed that the rank of ecacy within the same cell line varied less than in dierent cell lines.…”
Section: Comparisons Of Agents and Cell Linesmentioning
confidence: 53%